THE DEVELOPMENT OF THE LDII ORGANIZATION IN PALEMBANG CITY (2001–2022): A SOCIAL-HISTORICAL PERSPECTIVE: Perkembangan Organisasi LDII di Kota Palembang Tahun 2001–2022: Perspektif Sejarah Sosial - Farida R. Wargadalam; Muhammad Ghufron Firmansyah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the development of the Indonesian Islamic Propagation Institute (LDII) in Palembang City during the period 2001–2022 from a social history perspective. The study uses a qualitative approach with historical research methods through data collection from interviews, documentation, and observation. The analysis focuses on changes in organizational structure, religious roles, social roles, and economic empowerment. The results show that the development of LDII has been gradual and adaptive. In the period 2001–2005, LDII focused on organizational consolidation and internal development. The period 2006–2015 was marked by the strengthening of structures and the expansion of social roles. Furthermore, in the 2016–2022 period, LDII underwent modernization and digitalization in organizational management, da'wah, and economic empowerment. This study concludes that LDII is able to adapt to social and technological changes and play an active role in the life of the people of Palembang City.